Hi ChatGPT, Translate This Text into Easy Language: Is the New Easy Language Translator a Machine? - Christiane Maaß (VAKKI Publications)
We are surrounded by dysfunctional texts that are burdened with various communication barriers: They are not where we are looking for them, they are written in fonts that are too small, they are completely incomprehensible or unacceptable. Such texts make it difficult for us to act based on them and they need editing. Removing communication barriers is a form of translation. Accessible communication recognises and accommodates the diversity of communication partners. This diversity can be the result of differing interests and expertise in certain areas, differing educational opportunities, stressful life events such as flight or migration, but also disability. In recent years, accessible communication has become a major issue in Europe and around the world: Approaches include Easy Language, Plain Language, subtitling for the hearing impaired, text-to-speech interpreting, sign language interpreting, and audio description for the blind. An expert field has emerged here: It encompasses a labour market, study programmes, and scientific research. Recently, a new player has been added: artificial intelligence. Machine translation – between different languages, but also intralingually between different levels of comprehensibility – has recently improved enormously in quality. What does it entail that machine translation has become part of the field of accessible communication? Are human translators still necessary and what is their role? Who can use machine translation and for what? How is the field of accessible communication changing as a result? In this invited plenary talk of the XLIV VAKKI Symposium, held on 8-9 February 2024 at the University of Vaasa, I focus on Easy Language translation and try to find at least a preliminary answer to this question: Is the new Easy Language translator a machine?